Role of lectin receptors in recognition of Pseudomonas aeruginosa biofilms - Almuhanna, Yasir Saleh I (2021)
Colonisation and chronic lung infection by the opportunistic pathogen Pseudomonas aeruginosa (PA) is the leading cause of morbidity and mortality in cystic fibrosis patients. A critical key determinant of PA pathogenicity is the switch from planktonic to the biofilm mode of growth, which facilitates chronic infections and makes PA eradication extremely difficult. Biofilms are aggregates of microorganisms in which the cells are enclosed in an extracellular polymeric substance (EPS) that contains proteins, extracellular DNA (eDNA) and exopolysaccharides. Psl and Pel are two important exopolysaccharides utilised by PA to construct biofilms. While Psl is composed of D-mannose, D-glucose, and L-rhamnose, Pel contains N-acetylgalactosamine (GalNAc) and N-acetylglucosamine (GlcNAc).